Reasons for Use of and Experiences with Homeopathic Treatment as an Adjunct to Usual Cancer Care: Results of a Small Qualitative Study - Yde, Charlotte; Viksveen, Petter; Duckworth, Jean (Homeopathy, 2019)
Background A significant proportion of patients with cancer consult with homeopaths. No former qualitative study has reported on experiences with homeopathy in this patient group. This study aimed to learn about the reasons for, and experiences with, treatment provided by homeopaths among Danish patients with cancer.Methods A small qualitative semi-structured interview study was carried out to collect preliminary knowledge to learn about reasons for and experiences with treatment provided by homeopaths as an adjunct to usual care among patients with cancer. Thematic analysis was used for the development of themes.Results Five patients, diagnosed with cancer, were interviewed. On the basis of qualitative interviews five themes emerged: concerns and hopes, obstacles and support, internal health locus of control, whole person approach, and improved well-being.Conclusion The cancer patients in this study sought homeopathy to address their hopes and concerns and to help them face obstacles and find support. They were actively taking responsibility for their own health and valued the whole person approach used by their homeopaths. Participants reported improved well-being both at the physical and mental levels. The results provide a basis for further research to learn more from patients' experiences with this intervention. Such knowledge could potentially be helpful to improve healthcare practitioners' communication with patients, and thereby patients' overall care.
Keywords: qualitative; complementary and alternative medicine; homeopathy; cancer; thematic analysis